Analisis Butir Soal Ulangan Akhir Semester Bahasa Jepang Kelas XI Di SMA Negeri 1 Semarang: Analysis of Final Semester Exam Questions for Japanese Language Class XI at SMA Negeri 1 Semarang - Kolin, Anugrah Andriani; Rosliyah, Yuyun; Setiawati, Ai Sumirah; Oesman, Andy Moorad (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
Tests, as the evaluation tool most often used by educators to measure student learning outcomes, should be made well, correctly and of high quality. The formulation of the problem in this research is to look for the level of difficulty, differentiation power, effectiveness of distractors, quality of questions. The aim of this research is to determine the level of difficulty, differentiability, effectiveness of distractors, quality of Japanese UAS questions at SMA Negeri 1 Semarang. This research used descriptive quantitative methods with a sample of 72 students. The results of this research show that the level of difficulty of the questions is in the medium category, the differentiating power of the questions is included in the questions which are quite good, the effectiveness of the distractors shows that the questions are good, the quality of the questions as seen from the level of difficulty, the differentiating power, the effectiveness of the distractors shows quite good. There are 32 (80%) of the 40 questions that can be used as a good evaluation tool.